Q. 84.3( 10 Votes )

# In each of the fo

Answer :

We have,

*f*(*x*) = 3*x*^{4}+2*x*^{3} and *g*(*x*) = *x*+

Therefore, by remainder theorem when f (x) is divided by g (x) = x – (- ), the remainder is equal to f ()

Now, *f*(*x*) = 3*x*^{4}+2*x*^{3}

f () = 3 ()^{4} + 2 ()^{3} – () - +

= 3 * + 2 * - - +

= - - + +

= =

= 0

Hence, required remainder is 0.

Rate this question :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x^{31</s}RS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x^{3}RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics